# Find the product:$(i)$. $\frac{9}{2}\times(-\frac{7}{4})$$(ii). \frac{3}{10}\times(-9)$$(iii)$. $-\frac{6}{5}\times\frac{9}{11}$$(iv). \frac{3}{7}\times(-\frac{2}{5})$$(v)$. $\frac{3}{11}\times\ \frac{2}{5}$$(vi)$. $\frac{3}{-5}\times(-\frac{5}{3})$

Given:
$(i)$. $\frac{9}{2}\times(-\frac{7}{4})$

$(ii)$. $\frac{3}{10}\times(-9)$

$(iii)$. $-\frac{6}{5}\times\frac{9}{11}$

$(iv)$. $\frac{3}{7}\times(-\frac{2}{5})$

$(v)$. $\frac{3}{11}\times\ \frac{2}{5}$

$(vi)$. $\frac{3}{-5}\times(-\frac{5}{3})$

To do: To find the product of the given expression.

Solution:

$(i)$. $\frac{9}{2}\times(-\frac{7}{4})$

$=\frac{9\times(-7)}{2\times4}$

$=-\frac{63}{8}$

$=-7\frac{7}{8}$

$(ii)$. $\frac{3}{10}\times(-9)$

$=-\frac{27}{10}$

$=-2\frac{7}{10}$

$(iii)$. $-\frac{6}{5}\times\frac{9}{11}$

$=\frac{(-6)\times9}{5\times11}$

$=-\frac{54}{55}$

$(iv)$. $\frac{3}{7}\times(-\frac{2}{5})$

$=\frac{3\times(-2)}{7\times5}$

$=-\frac{6}{35}$

$(v)$. $\frac{3}{11}\times\ \frac{2}{5}$

$=\frac{3\times2}{11\times5}$

$=\frac{6}{55}$

$(vi)$. $\frac{3}{-5}\times(-\frac{5}{3})$

$=\frac{3\times(-5)}{(-5)\times3}$

$=\frac{-15}{-15}$

$=1$
Tutorialspoint

Simply Easy Learning

Advertisements